Multimodal Extensive Reading: Students’ Affective Attitudes towards Reading Comprehension - Mega Mulianing Maharani; Sri Wuli Fitriati; Novia Trisanti; Mega Mulianing Maharani; Sri Wuli Fitriati; Novia Trisanti (Universitas Negeri Malang, 2026)
Knowing the importance of technology integration brings a new solution for extensive reading class. A multimodal extensive reading was implemented in order to monitor the students’ mental condition towards reading comprehension. Considering multiple analysis on multimodal approach implementations in second language classroom, this current study connects it in extensive reading in order to investigate how students’ affective attitudes towards reading comprehension are shown among students participating in a multimodal extensive reading. The study was designed as quantitative research. The participants were 15 undergraduate students who enrolled in an extensive reading in a private university in Semarang. A closed-ended questionnaire was used to collect the data. Then it was analyzed statistically through SPSS to get the result. The result of the study has revealed that the students showed their affective attitudes positively towards reading comprehension in a multimodal extensive reading. It was proved from the statistical analysis results that 2 statements received 80% strongly agree responses; 2 statements were 73.3% responded as strongly agreed; 2 statements were 66.7% responded as strongly agreed; and 4 statements were 60% responded as strongly agreed. The students show positive attitudes towards reading comprehension as the feeling on multimodal extensive reading implementation.